Poe, Baudelaire, Huysmans: dândis e malditos - Camargo, Luciana Moura Colucci de (2014)
Poe, Baudelaire and Huysmans, voices that bewilder readers due to their literary iconoclastic impulse, knew how to bother society and tradition becoming archetypes of the poèt maudit. Eccentrics, these poets, living exiled to the margins of the frustrated bourgeois society with its moral rules, wish for something beyond world then was offering; so, they turn for the mysterious regions of the obscure, of the sordidness and of the Satanic, finally becoming the poets of the abyss. At the same time maudits and aesthetes, they wish to be sublime and consider the dandyism like the last ray of light of the decadence: it is what this article intends to discuss.